Micro Operator Design Pattern in 5G SDN/NFV Network. (10th July 2018) - Tseng, Chia-Wei; Huang, Yu-Kai; Tseng, Fan-Hsun; Yang, Yao-Tsung; Liu, Chien-Chang; Chou, Li-Der
Abstract : The trend of 5G mobile networks is increasing with the number of users and the transmission rate. Many operators are turning to small cell and indoor coverage of telecom network service. With the emerging Software Defined Networking and Network Function Virtualization technologies, Internet Service Provider is able to deploy their networks more flexibly and dynamically. In addition to the change of the wireless mobile network deployment model, it also drives the development trend of the Micro Operator ( μ O). Telecom operators can provide regional network services through public buildings, shopping malls, or industrial sites. In addition, localized network services are provided and bandwidth consumption is reduced. The distributed architecture of μ O tackles computing requirements for applications, data, and services from cloud data center to edge network devices or to the micro data center of μ O. The service model of μ O is capable of reducing network latency in response to the low-latency applications for future 5G edge computing environment. This paper addresses the design pattern of 5G micro operator and proposes a Decision Tree Based Flow Redirection (DTBFR) mechanism to redirect the traffic flows to neighbor service nodes. The DTBFR mechanism allows different μ Os to share network resources and speed up the development of edge computing in the future.